Adjustment Difficulties and Cognitive Counseling Intervention in a 10th-Grade Vocational High School Student - Andrea Grazita Snait; Karolin Rista (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
This study aims to understand the dynamics of adjustment in a 10th-grade vocational high school student who experiences difficulties adapting to a new school environment. The subject is a 16-year-old female student who showed significant behavioral changes from being active and socially engaged to becoming withdrawn, quiet, and experiencing social anxiety after entering the new school. The methods used include interviews, observations, and psychological assessments (16 PF, DAP, BAUM, and HTP). The assessment results indicate tendencies toward social anxiety, overthinking, distrust of the social environment, and a strong need for social acceptance. Contributing factors include negative past experiences, environmental changes, and maladaptive thought patterns. The intervention was conducted through individual counseling using a cognitive approach combined with relaxation techniques and social skills training. The results show improvements in self-awareness, anxiety management, and the emergence of initiative in social interactions. However, the client still exhibits overthinking in certain situations. Overall, the intervention is considered effective in supporting the adjustment process, with a favorable prognosis if supported by a conducive environment and consistent follow-up interventions.